Molecular Signatures of Tissue-Specific Microvascular Endothelial Cell Heterogeneity in Organ Maintenance and Regeneration - Nolan, Daniel J.; Ginsberg, Michael; Israely, Edo; Palikuqi, Brisa; Poulos, Michael G.; James, Daylon; Ding, Bi-Sen; Schachterle, William; Liu, Ying; Rosenwaks, Zev; Butler, Jason M.; Xiang, Jenny; et al. (Developmental cell, 2013)
Microvascular endothelial cells (ECs) within different tissues are endowed with distinct but as yet unrecognized structural, phenotypic, and functional attributes. We devised EC purification, cultivation, profiling, and transplantation models that establish tissue-specific molecular libraries of ECs devoid of lymphatic ECs or parenchymal cells. These libraries identify attributes that confer ECs with their organotypic features. We show that clusters of transcription factors, angiocrine growth factors, adhesion molecules, and chemokines are expressed in unique combinations by ECs of each organ. Furthermore, ECs respond distinctly in tissue regeneration models, hepatectomy, and myeloablation. To test the data set, we developed a transplantation model that employs generic ECs differentiated from embryonic stem cells. Transplanted generic ECs engraft into regenerating tissues and acquire features of organotypic ECs. Collectively, we demonstrate the utility of informational databases of ECs toward uncovering the extravascular and intrinsic signals that define EC heterogeneity. These factors could be exploited therapeutically to engineer tissue-specific ECs for regeneration. [Display omitted] •Standardized protocols allow profiling of EC heterogeneity•Molecular signatures that define tissue-specific ECs•ETS-family transcription factors as modulators of tissue-specific vascular function•In vivo transplantation and in vitro differentiation models to study heterogeneity Endothelial cells are now appreciated as a source of complex combinations of growth factors, known as Angiocrine factors, which direct tissue-specific microenvironments. Nolan et al. transcriptionally profiled microvascular endothelial cells from steady-state and regenerating tissues to create a database capable of identifying the characteristics of endothelial cell heterogeneity.